Governance and institutional frameworks in Ethiopian Integrated Agro-Industrial Parks: Enhancing innovation ecosystems and multi stakeholder coordination for global market competitiveness - Efa Muleta Boru; Junseok Hwang; Abdi Yuya Ahmad (Economies, 2025)
This study investigates the interrelationships between institutional frameworks, innovation ecosystems, and stakeholder coordination in enhancing the global competitiveness of Ethiopia's Integrated Agro-Industrial Parks (IAIPs) in Yirgalem and Bulbula. A mixed-methods approach combining qualitative thematic analysis, Partial Least Squares Structural Equation Modeling (PLS-SEM), and SWOT analysis was employed to evaluate the influence of governance structures on innovation and competitiveness. Findings suggest that while strong institutional frameworks and effective stakeholder coordination foster innovation, a misalignment between the innovation ecosystem and global market demands limits competitiveness. Rigid institutional structures hinder IAIPs' adaptability to market fluctuations. Future research should explore the role of digital transformation, such as digital agriculture tools and traceability systems, in enhancing competitiveness. Additionally, examining the influence of public-private partnerships and conducting longitudinal studies on adaptive governance's effect on IAIP resilience could provide valuable insights for the development of Ethiopia's agro-industrial sector. The study underscores the need for flexible, market-responsive frameworks and enhanced stakeholder engagement.
Keywords: 330; innovation ecosystem; governance framework; integrated agro-industrial parks; global competitiveness; Ethiopia; stakeholder coordination